2010
DOI: 10.1213/ane.0b013e3181b845b0
|View full text |Cite
|
Sign up to set email alerts
|

Preamputation Mirror Therapy May Prevent Development of Phantom Limb Pain: A Case Series

Abstract: We report the cases of 4 patients who performed daily mirror therapy for 2 wk before undergoing elective limb amputation. One patient experienced no phantom limb pain (PLP). Two patients experienced rare episodes of mild PLP without effect on their participation in physical therapy (PT) or their quality of life. One patient reported daily, brief episodes of moderate PLP without effect on his participation in PT or his stated quality of life. These results indicate that preoperative mirror therapy may improve p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0
6

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 11 publications
0
32
0
6
Order By: Relevance
“…[13,14,[26][27][28][29][30] It is a method that can be used independently by nurses to manage the care of a patient with PLP. In addition, it provides a great opportunity for amputees to be able to manage their pain themselves.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[13,14,[26][27][28][29][30] It is a method that can be used independently by nurses to manage the care of a patient with PLP. In addition, it provides a great opportunity for amputees to be able to manage their pain themselves.…”
Section: Discussionmentioning
confidence: 99%
“…There are certain findings which proove that mirror therapy decreases PLP by helping the regression of changed cortical map. [28][29][30][31][32][33][34][35][36][37][38][39] Patients with cosmetic prostheses took off the prostheses only when practicing mirror therapy. For a large portion of the day, they were wearing the prosthesis, and thus, may be blocking possible positive effect of mirror therapy on their cortical brain map.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pathophysiology of PLP is still unknown and is not completely understood, therefore provides a challenge to those involved in the management and treatment of this pain [7]. It has been shown that a range of treatments such as pharmacological treatment, neuromodulation, physical treatment, nerve block and surgical treatment has been unsuccessful in treating PLP and any efficacious methods have yet to be proven [1,8]. …”
Section: Letter To Editorsmentioning
confidence: 99%
“…It was shown that one of the patients experienced no PLP. Rare episodes of mild PLP were experienced by two of the patients, without affecting their quality of life or their participation in physical therapy; one patient reported daily, brief episodes of moderate PLP without any effect on his participation in physical therapy or his stated quality of life [8]. In addition, Kim et al reported the successful reduction of PLP in a 30-year-old male patient with an above-elbow amputation using mirror therapy.…”
Section: Letter To Editorsmentioning
confidence: 99%